2011
DOI: 10.2149/tmh.2010-19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and insecticide susceptibility of dengue vectors in the district of Batticaloa in eastern Sri Lanka

Abstract: Unprecedented incidences of dengue have been reported in Sri Lanka in recent years. The district of Batticaloa, which was devastated by the 2004 Asian tsunami, is one of the districts affected by dengue. One option to curtail this disease is to implement appropriate vector control measures. A nine-month study was carried out within the Batticaloa Municipal Council limit from April to December 2008. Larval collections were conducted fortnightly using conventional ovitraps for nine months covering the dry and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…are resistant to insecticide in indoor or outdoor spraying. A study conducted in Sri Lanka showed Aedes aegypti and Aedes albopictus were highly resistant to DDT and they can oviposit indoors and outdoors [14]. Another study in Bangladesh reported abundant potential larval habitats for Aedes sp.…”
Section: Discussionmentioning
confidence: 99%
“…are resistant to insecticide in indoor or outdoor spraying. A study conducted in Sri Lanka showed Aedes aegypti and Aedes albopictus were highly resistant to DDT and they can oviposit indoors and outdoors [14]. Another study in Bangladesh reported abundant potential larval habitats for Aedes sp.…”
Section: Discussionmentioning
confidence: 99%
“…Aedes aegypti tends to predominate during the pre-monsoon season and Aedes albopictus during the monsoon season. Since the monsoon rain in Batticaloa district from October to December, the density of Aedes mosqutoes increases during this period and a positive association between rainfall and Aedes density has been observed [5].…”
Section: Fig 1 Map Of Sri Lanka (Eastern Province Has Been Colored)mentioning
confidence: 90%
“…Also there was a positive relationship between the number of Aedes eggs and rainfall and humidity but not with temperature. Dharshini et al also conducted Aedes egg survey and larval survey in Batticaloa district of Sri Lanka [5]. They observed a positive association between rainfall and Aedes density.…”
Section: Fig 1 Map Of Sri Lanka (Eastern Province Has Been Colored)mentioning
confidence: 99%
See 2 more Smart Citations